EFFORTS TO INCREASE MATHEMATICS LEARNING OUTCOMES FOR FLAT BUILDING MATERIALS THROUGH STAD TYPE COOPERATIVE MODEL SIFAT BANGUN DATAR MELALUI MODEL - Retno Maya Sealviana Firanti; Agung Setyawan (Citra Dharma Cindekia, 2022)
Mathematics is a subject that is often considered difficult for some students, even though mathematics is always needed in all fields of science and to solve problems in everyday life. However, based on a preliminary study conducted in class III SDN Tunjung 4, the teacher uses the lecture model continuously so that it has an impact on students' low mathematics learning outcomes. The purpose of this study was to improve the mathematics learning outcomes of third grade students of SDN Tunjung 4 on flat-shaped materials through the application of the STAD type cooperative learning model. The method used is interviews, observations, tests, and documentation with data analysis techniques in the form of quantitative data analysis techniques. The results showed an increase in student learning outcomes in mathematics. This is shown from the average posttest score of learning outcomes in the first cycle, which is 63.75 with a percentage of students who complete 40%. The results increased in the second cycle, where the average score obtained was 77 with the percentage of students completing 85%. Based on the results of this study, it can be concluded that the STAD type cooperative learning model can improve the mathematics learning outcomes of third grade students of SDN Tunjung 4 on the flat shape material.